Desenvolvimento e aplicação de sensor eletroquímico obtido por eletrofiação de polímeros e nanotubos de carbono - Gusmão, Ana Paula (2019)
Contamination and environmental pollution by chemical substances have become increasingly frequent. The detection of these substances in the environment, which may present high risk to society, has been possible due to the scientific advancement that seeks solutions for this problem. Thus, this work stands out for seeking the development of an electrochemical sensor for the determination of analytes of environmental interest. The electrochemical sensor was developed from polymeric fibers with multiple-walled carbon nanotubes (MWCNT's). These fibers were obtained by electrospinning using the PBAT/ PLA polymer in chloroform and dimethylformamide solution. The parameters used were: flow 1,80 mL h-1, distance between the needle and the target collector: 16 cm, and voltage: 18 kV. The morphological characterization of the formed film showed possible interaction between the polymers and the MWCNT's, and according to transmission electron microscopy (TEM) and contact angle analyzes, they are inside the formed fibers. The interaction can also be noticed due to changes in film degradation temperatures (TGA), increased crystallinity (DSC and XRD) and changes in mechanical properties. Although interaction may have occurred, the addition of MWCNTs did not cause a change in the mean diameter of the fibers (2,24 μm without and 2,23 μm with MWCNT's). After the film was obtained, it was heat treated for 5 hours at 550 °C and the material obtained was used to prepare a suspension of chitosan that was added on the surface of a glassy carbon electrode. To evaluate the functionality of the sensor, it was tested for metronidazole (MTZ) using cyclic voltammetry (CV), where it was noted that the electrode built by electrospinning showed higher current intensity when compared to the conventional method of obtaining sensors using MWCNT's. In addition, this sensor was used to develop a methodology for 2,4,6-Trichlorophenol (2,4,6 TCP) which is considered an environmental pollutant of a carcinogenic character and of low biodegradability. Initially, studies were carried out with cyclic voltammetry, showing that the analyte presented an irreversible oxidation peak at 0,710 V with the process controlled by the diffusion of the species. The development of the methodology was performed using square wave voltammetry (SWV), and the best electrochemical responses for the optimized parameters were: frequency 150 Hz; amplitude 50 mV and increase 7 mV. After optimization, the analytical curve was constructed in duplicate in the concentration range of 1,00x10-6 to 2,00x10-5 mol L-1. The detection limit was 1,09x10-6 mol L-1 (0,21 mg L-1), a value close to that allowed by the Ministry of Health in drinking water (0,20 mg L-1), indicating that the methodology is promising for the determination of 2,4,6 TCP in water for human consumption.